Underlying processes behind false perspective production - Manzanero, Antonio L; López, Beatriz; Aróztegui, Javier (Anales de Psicología / Annals of Psychology, 2015)
This study aimed to determine the extent to which content analysis can provide useful information when discriminating between actual versus false statements. Participants were instructed to either describe a traffic accident as eyewitness actual role or to describe the accident as a simulated victim. Data were analysed in terms of accuracy and quality, and were represented using high dimensional visualization (HDV). In Experiment 1 (between-participant design), participants made significantly more references to cognitive operations, more self-references and less changes in order when describing the event as simulated victim. In Experiment 2 (within-participants design) participants also made significantly more references to cognitive operations and more self references when describing the event from the simulated victim as well as being less accurate, providing less irrelevant information and more evaluative comments. HDV graphics indicated that false statements differ holistically from actual ones.